Analysis of prevention through design studies in construction: A subject review - Jin, Ziyu; Gambatese, John; Karakhan, Ali; Nnaji, Chukwuma (Journal of safety research, 2023)
•Reviewed 140 articles about Prevention through Design (PtD) in construction.•Identified an increasing trend in PtD publications between 2008 and 2020.•Previous work centers on PtD resources/tools/procedures and technology applications.•Findings provide a basis for future research related to PtD.•Findings provide implications for practitioners adopting PtD and selecting PtD tools. Introduction: The concept of addressing and minimizing construction site safety risks in the early phase of a project has generated research interest, especially since the National Institute for Occupational Safety and Health (NIOSH) launched its national Prevention through Design (PtD) initiative in July 2007. In the last decade, several studies on PtD with differeing goals and methods have been published in construction journals. To date, few systematic examinations of the development and trends associated with PtD research have been conducted in the discipline. Method: This paper presents a study of the latest PtD research trends in construction safety management through analysis of publications in prominent construction journals from 2008 to 2020. Both descriptive and content analyses were conducted based on the number of papers published annually and clusters of topics covered in the papers. Results: The study shows an increasing interest in PtD research in recent years. Research topics covered mainly focus on the perspectives of PtD stakeholders, PtD resources/tools/procedures, and technology applications to facilitate PtD implementation in practice. This review study provides an improved understanding of the state-of-the-art of PtD research in terms of accomplishments and research gaps. The study also compares the findings from journal articles with industry best practices related to PtD to guide future research in this domain. Practical Application: This review study is of significant value to researchers to overcome the limitations of the current PtD studies, and to extend the scope of PtD research, and can be used by industry professionals when considering and selecting appropriate PtD resources/tools in practice.